2007
DOI: 10.1007/s12022-007-9006-y
|View full text |Cite
|
Sign up to set email alerts
|

P53 Gene Mutations in Pituitary Carcinomas

Abstract: Although p53 overexpression detected by immunohistochemistry has been reported in pituitary adenomas and carcinomas, genetic mutations in the p53 gene have not been previously detected in these tumors. We analyzed a series of eight pituitary adenomas and six pituitary carcinomas by immunohistochemistry, polymerase chain reaction amplification, and sequencing of p53 exon 5 through exon 8 for genetic mutations. Three carcinomas showed more than 20% expression of p53 protein in the tumor cells. One of these tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 24 publications
(44 reference statements)
0
45
1
1
Order By: Relevance
“…Whereas p53 is usually undetectable in healthy cells due to rapid degradation, mutations in the TP53 gene can lead to overexpression of oncogenic p53 in cancer cells (Janicke et al 2008). Because TP53 mutations have only rarely been detected in pituitary adenomas, mutationrelated p53 upregulation seems not very feasible (Suliman et al 2001, Tanizaki et al 2007). However, oxidative stress is a general feature of cancer cells, going along with DNA damages and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas p53 is usually undetectable in healthy cells due to rapid degradation, mutations in the TP53 gene can lead to overexpression of oncogenic p53 in cancer cells (Janicke et al 2008). Because TP53 mutations have only rarely been detected in pituitary adenomas, mutationrelated p53 upregulation seems not very feasible (Suliman et al 2001, Tanizaki et al 2007). However, oxidative stress is a general feature of cancer cells, going along with DNA damages and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in proto-oncogenes like KRAS, RET, PTTG and c-MYC and in tumor suppressors like RB1 are very rarely reported in corticotrophinomas (10). Mutations in the p53 gene (TP53) are extremely rare and were found only in atypical corticotroph (i.e., aggressive) tumors and carcinomas (11,12). CD is rarely seen in the context of genetic syndromes like multiple endocrine neoplasia MEN1 (MEN1 encoding menin), MEN4 (CDKN1B encoding p27/KIP1), McCuneAlbright syndrome (GNAS oncogene encoding the stimulatory G protein Gsa) and never in Carney complex (PRKAR1A) (13,14,15).…”
Section: Genetic Events In CDmentioning
confidence: 99%
“…Based on this hypothesis, MDM2 protein expression in hypophyseal tumors was first demonstrated in a study by Suliman et al (19). Although p53 is one of the most frequently inactivated genes in human cancer, p53 mutation was very rarely detected in hypophyseal adenomas (34,35). As a possible explanation for this, it was suggested that in the pathogenesis of hypophyseal tumors, the effect of cellular stress on p53 pathway could be more important than mutations in p53 and that p53 may not initiate tumor development, but could play a role in prognosis (36).…”
Section: Discussionmentioning
confidence: 99%